Measuring network effects of digital industrial platforms: towards a balanced platform performance management - Fabian Schüler; Dimitri Petrik (Information Systems and e-Business Management, 2023)
Firms increasingly establish digital industrial platforms to cope with the adaption of the industrial internet of things (IIoT) paradigm. The tremendous success of digital platforms in many platform-mediated industries can be traced back to the ignition of network externalities. However, the impact of network externalities is still under discussion in the IIoT domain, and their measurement remains a challenge for platform companies. This paper outlines how network effects were measured in the existing research, deriving three dimensions of network effects for IIoT: (1) ecosystem utility, (2) complementarity, and (3) compatibility. This conceptualization is further used in an empirical study with practitioners from digital industrial platform organizations to enable performance measurement of network effects in IIoT by developing 20 key performance indicators (KPIs). Based on the empirical study results, this paper proposes a framework for balanced platform management. Utilizing the goals of a balanced scorecard, the framework emphasizes the trade-off between the contradicting perspectives on costly network effect simulation and platform earnings that platform managers need to balance. The KPI portfolio can support platform managers in implementing the framework.
Keywords: 650; Industrial internet of things; Digital industrial platforms; Network effects; Performance measurement; KPIs; Balanced scorecard